A Comprehensive Review of Polycystic Ovary Syndrome (PCOS): Pathophysiology, Diagnosis and Management - Pankti Bhavik kumar Patel; Amar M. Raval; Helly Bhupendrabhai Patel; Krisha Hiteshbhai Patel; Patel Poorv; Purva Ajesh Kumar Vaidya; Krishna Hiteshkumar Kahar (Asian Journal of Pharmaceutical Research and Development, 2026)
Polycystic Ovary Syndrome (PCOS) is one of the most prevalent endocrine and metabolic disorders affecting women of reproductive age worldwide. It is characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology. Beyond reproductive abnormalities, PCOS is strongly associated with insulin resistance, obesity, dyslipidemia, and chronic low-grade inflammation, predisposing affected individuals to type 2 diabetes mellitus, cardiovascular disease, and endometrial hyperplasia. The pathophysiology of PCOS is multifactorial, involving genetic predisposition, neuroendocrine dysregulation, metabolic disturbances, and environmental influences. Diagnosis is primarily based on the Rotterdam consensus criteria. Management strategies include lifestyle modification, pharmacological therapy tailored to symptom profile, and fertility-directed interventions where required. This review comprehensively summarizes the epidemiology, mechanisms, clinical manifestations, diagnostic criteria, therapeutic approaches, and emerging trends in PCOS management.